2018
DOI: 10.1016/j.jnca.2018.03.022
|View full text |Cite
|
Sign up to set email alerts
|

L-CAQ: Joint link-oriented channel-availability and channel-quality based channel selection for mobile cognitive radio networks

Abstract: Channel availability probability (CAP) and channel quality (CQ) are two key metrics that can be used to efficiently design a channel selection strategy in cognitive radio networks. For static scenarios, i.e., where all the users are immobile, the CAP metric depends only on the primary users' activity whereas the CQ metric remains relatively constant. In contrast, for mobile scenarios, the values of both metrics fluctuate not only with time (time-variant) but also over different links between users (link-varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The learning process always needs to find a relation between the features to increase the learning regression accuracy [99]. For instance, using features of a physical layer, i.e., CAP, CQ, and LI can train it to estimate the link-throughput [88]. Hence, supervised first must train the algorithm on this data to learn how to estimate link-throughput for the smart routing protocol and that it can make the CU smarter to select the higher throughput link and can increase the routing efficiency.…”
Section: ) Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The learning process always needs to find a relation between the features to increase the learning regression accuracy [99]. For instance, using features of a physical layer, i.e., CAP, CQ, and LI can train it to estimate the link-throughput [88]. Hence, supervised first must train the algorithm on this data to learn how to estimate link-throughput for the smart routing protocol and that it can make the CU smarter to select the higher throughput link and can increase the routing efficiency.…”
Section: ) Sample Collectionmentioning
confidence: 99%
“…The physical layer must be vigilant to any varying in licensed channel availability. Because of the mobility of CU and PU, physical layer jobs to detect the PU signal on the licensed channel become a daunting task [88]. Numerous studies have focused on spectrum sensing to identify PU signal [12].…”
Section: E Physical Layer Challenge In Mobile Cognitive Radio Networkmentioning
confidence: 99%
“…For the proper operation of the CRN, the SU nodes must be able to sense the environment, select the best channel from the available choices for utilization, coordinate handoff in case of arrival of PU and ensure uninterrupted services [16]- [17]. It is also important for the SU to maintain the Quality of Service (QoS) above the minimum threshold during all these operations.…”
Section: B Spectrum Handoff Processmentioning
confidence: 99%
“…However, some literatures have considered channel quality as well as channel availability as important metrics for channel selection in CRNs. In [32], authors showed that channel availability as well as channel quality are the two significant metrics that should be considered when designing an efficient CSS. In their work, an L-CAQ channel selection scheme was design, which selects channel that jointly maximizes channel availability probability as well as channel quality.…”
Section: Related Workmentioning
confidence: 99%